Design, construction, testing and performance evaluation of manually operated four (4) row rice hill seeder for wetland paddy - Lacayanga, Jonathan E. (Philippine agricultural mechanization journal)
Direct seeding method of rice cultivation has gained wide range of acceptability to small farmer's majority of whom produces rice throughout the year. With the existing design of seeders used in direct seeding both for hybrid and inbred rice, recommendations prevails as to its design. The basis of the design was focused in generating actual information on the seeder metering mechanism that will constitute a hill similar to the transplanted rice, the appropriate and simplest design of metering activator the seeder capacity, seeding rate, seeding efficiency, percent missed hills and the seeder cost and its operation. The prototype seeder was designed and fabricated for the purpose of further reducing the direct seeding cost, improve crop establishment, increase efficiency and capacity and to capture a wider range of acceptability to farmers engaged in direct seeding. The seeder was made from locally available materials where some can easily be acquired from second hand shop or junk shop. It can easily be fabricated without requiring technical skills and ability. The seeder is manually operated by only one person. It is light in weight (7.20 kg without seeds), thus reducing the drudgery of pulling. The seeder consists of major parts like the ground wheel furrow opener, ski, main frame where all parts are attached to it and the pulling handle. The most important part is the seed metering and hopper assembly that has the ability to accommodate and drop 2-3 seeds per hill spaced at 20 cm between rows and hills. On a well prepared paddy, the seeder was tested using three (3) rice varieties namely PSB Rc 66 considered high yielding, SL-8 hybrid rice and Dinorado a fancy inbred rice variety. The purpose was to determine whether the seeder would perform using different rice seed varieties. Field tests showed there was no significant difference in parameters under observation using 3 rice varieties. It includes seeding rate (kg/ha), Seeding efficiency (%), Field capacity (ha/hr), Field efficiency (%) and Percent missed hills (%). During the actual field testing, an average forward speed of 1.61 km/hr was maintained. Under this condition, tests revealed the seeder achieved an effective Field capacity of 0.631 ha/day, Field efficiency of 65.22 percent, Work capacity of 8.239 hr/ha, Seeding rate of 16-20 kg/ha and Missed hills of 13.79 percent, seeding efficiency of 83.11 percent and acceptable -6.12 percent slippage. With an initial costs of Php2,164.80, considering that a custom rate / ha of Php 1,200/ ha the seeder must be operated at a rate of 0.607 ha / year (607 square meters) to break even.